Esterco bovino para o desenvolvimento inicial de plantas provenientes de quatro matrizes de Corymbia citriodora - Costa, Fabiana Gorricho [UNESP]; Valeri, Sérgio Valiengo [UNESP]; Cruz, Mara Cristina Pessôa Da [UNESP]; Gonzales, José Luis Soto [UNESP] (My University, 2011)
This work aimed to evaluate the effect of cattle manure levels in the phase of implementation Corymbia citriodora (Hook.) K. D. Hill & L. A. S. Johnson (Eucalyptus citriodora) seedlings in field, produced from seeds collected from four mother trees. The experiment was carried out in green house, in pots filled with 5 dm 3 of Oxisol. Five cattle manure levels were applied 0, 10, 20, 30, and 40 t ha -1 (0, 25, 50, 75, and 100 g pot -1). All treatments received lime levels which were calculated to increase the base saturation degree to 50%. The soil fertility was evaluated after 30 days of soil incubation with manure and lime. The seeds were collected from mother trees called 2, 8, 20 and 29. Sowing was performed directly in rigid plastic containers of 50 cm 3 and seedlings were transplanted when they were around 17 cm height. The experimental design was entirely randomized, in a factorial 5 × 4 (five doses of cattle manure and seeds of four mother trees) scheme and four repetitions. Each parcel was a pot with two plants. At 90 days the height, foliar area, stalk diameter, shoot and root dry matter. The plants responded positively to application of manure, but differently for each evaluated growth characteristic linearly or quadratically. The manure levels had linear effects on growth characteristics and dry matter production of the plants from mother trees 2 and 20 moreover these plants require more cattle manure levels than ones from mother trees 8 and 29. The cattle manure promoted the best development of plants from mother trees 8 and 29, in relationship with dry matter production of shoot components was approximately 27 t ha-1, equivalent to 67.5 g pot.
Cattle manure for the initial development of plants from different mother of Corymbia citriodora
Keywords: Eucalyptus; Organic fertilization; Oxisol; Cattle manures; Corymbia; Dry matter production; Growth characteristic; In-field; Root dry matter; Saturation degree; Soil fertility; Soil incubation; Lime; Plant extracts; Plastic containers; Rating; Seed; Manures